2004
DOI: 10.1590/s1516-35982004000800006
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo do capim-Tanzânia (Panicum maximum Jacq. cv. Tanzânia-1) pastejado em diferentes alturas

Abstract: RESUMO -Avaliaram-se as concentrações de proteína bruta (PB), de fibra em detergente neutro (FDN), de fibra em detergente ácido (FDA), de fósforo (P), de potássio (K), de cálcio (Ca) e de magnésio (Mg) e a digestibilidade in vitro da matéria seca (DIVMS) nas frações lâminas foliares e colmos + bainhas em pastagem de capim-Tanzânia (Panicum maximum Jacq. cv. Tanzânia-1) manejada em quatro alturas de dossel forrageiro (20, 40, 60 e 80 cm). O método de pastejo foi o de lotação contínua, com taxa de lotação variáv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
(18 reference statements)
0
8
0
21
Order By: Relevance
“…Aruana, Tanzânia, Vencedor, PM40, PM43 and PM46 presented the highest values of OMD. In Tanzânia pastures managed with four sward heights (0.2, 0.4, 0.6 and 0.8 m) OMD of leaves decreased linearly from 740 to 670 g kg -1 as sward height increased (Cano et al, 2004). As expected, OMD showed a high negative correlation with ADF (-0.67; p < 0.001) and moderately negative with NDF (-0.37; p < 0.001) and a positive correlation with CP (0.80; p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Aruana, Tanzânia, Vencedor, PM40, PM43 and PM46 presented the highest values of OMD. In Tanzânia pastures managed with four sward heights (0.2, 0.4, 0.6 and 0.8 m) OMD of leaves decreased linearly from 740 to 670 g kg -1 as sward height increased (Cano et al, 2004). As expected, OMD showed a high negative correlation with ADF (-0.67; p < 0.001) and moderately negative with NDF (-0.37; p < 0.001) and a positive correlation with CP (0.80; p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
“…For high yielding tropical grasses managed under intermittent stocking, use of targets such as sward height in the pre-and post-grazing helps to control the growth of stems that can be harmful to intake and cattle performance Benvenutti et al, 2008). For the same reason, continuous stocking management is not recommended for P. maximum because of its tendency towards heterogeneity in sward structure that results in patches with excessive stem growth, although Tanzania pastures had been assessed by continuous stocking systems too (Cano et al, 2004). So, the choice of productive species with a high proportion of leaves, a better quality plant component than stems is benefi cial.…”
Section: Resultsmentioning
confidence: 99%
“…Entende-se como valor nutritivo a concentração e digestibilidade de nutrientes junto com a natureza da digestão dos produtos finais (MOTT & MOORE, 1970). Por isso, é importante o estudo da composição química da forragem e sua digestibilidade, a fim de conhecer a qualidade do pasto ao qual os animais terão acesso em pastejo (CANO et al, 2004). O valor nutricional de plantas forrageiras é dependente principalmente da proporção entre tecidos de alta e de baixa digestibilidade, o que pode explicar diferenças qualitativas entre espécies e/ou cultivares (WILSON, 1997).…”
Section: Introductionunclassified
“…In a study on Mombasa-grass subjected to intermittent stocking strategies, Da Silva et al (2009) observed that pre-and postgrazing forage masses were lower with 95% light interception treatments compared with 100% light interception; however, the proportion of leaves was higher and the proportion of stems and dead plant material was lower in the former treatment. Cano et al (2004) studied Tanzaniagrass and concluded that the nutritional value of leaf blades was higher compared with the stem + sheath fraction, regardless of forage canopy height and study duration, indicating that grass management should focus on the contribution of leaf forage mass. As a rule, prolonged regrowth periods of species exhibiting early stem elongation make it more difficult to control the forage canopy, and this might limit subsequent leaf blade accumulation and the production of high-quality forage.…”
Section: Introductionmentioning
confidence: 99%